The Role Of The Legal System And Law Enforcement In Handling Crimes Of Corruption: A Comparative Analysis Of Indonesia, Malaysia, And Thailand - Gaol, Michael Yudhistira Lumban; Majid, Abdul; Afandi, Fachrizal (Faculty of Law, Universitas Pekalongan, 2024)
The criminal act of corruption that is rampant in the country is not only detrimental to state finances but is a violaton of the social and economic rights of society at large, corruption is no longer a national problem, but has become a transnational phenomenon so that internatonal cooperaton is essential in preventing and eradicating it. , in fact, for what has been caused by the crimnal act of corrupton, extraordinary efforts are needed in terms of prevention and eradication of crimnal acts of corruption. One of the efforts to prevent Indonesia from falling due to corruption is to confiscate and return assets resulting from corrupton crimes based on the laws and regulations in force in the Indonesan legal system. in Indonesia, there is no uinfied institution that has the right to deal with corruption. The eradication of corruption in Indonesia is carred out by 3 state institutions, namely the Attorney General's Office, the Police, and the Corrupton Eradication Commission (KPK). The eradication of corruption in one country will not run optimally if it is not supported by the government's political will to eradicate corruption, the unity of state institutions that eradicate corrupton, and the enforcement of existing corrupton eradication regulations.